1994
DOI: 10.1073/pnas.91.19.8731
|View full text |Cite
|
Sign up to set email alerts
|

The development of mitochondrial medicine.

Abstract: Primary defects in mitochondrial function are implicated in over 100 diseses, and the list continues to grow. Yet the first mitochondrial defect-a myopathy-was demonstrated only 35 years ago. The field's dramatic expansion reflects growth of knowledge in three areas: (i) characterization of mitochondrial structure and function, (i) euiation of the steps involved in mitochondrial biosynthesis, and (Ni) discovery of specific mitochondrial DNA. Many mitochondrial diseases are accompanied by mutations in this DNA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0
3

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(99 citation statements)
references
References 154 publications
2
94
0
3
Order By: Relevance
“…Free radicals, such as reactive oxygen and nitrogen species, are normally generated during energy production in mitochondria. Excess levels of these radicals can negatively affect mitochondrial function through oxidative damage of mitochondrial macromolecules (35,36). Because non-protein-bound iron can generate free radicals through Fenton chemistry, we studied the effect of iron overload associated with hemochromatosis on oxidative damage and mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%
“…Free radicals, such as reactive oxygen and nitrogen species, are normally generated during energy production in mitochondria. Excess levels of these radicals can negatively affect mitochondrial function through oxidative damage of mitochondrial macromolecules (35,36). Because non-protein-bound iron can generate free radicals through Fenton chemistry, we studied the effect of iron overload associated with hemochromatosis on oxidative damage and mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%
“…OS-caused alteration of mitochondrial functions can manifest in different manners (Cardoso et al, 1999). Leakage of free radicals from the respiratory chain leads to damaged mitochondrial membrane, proteins, DNA and inhibits oxidative phosphorylation (Luft, 1995;. Maneiro et al (2003) found inhibition of functions of complex II and III of the respiratory chain and higher frequency of energetically "exhausted" mitochondria in chondrocytes of patients with osteoarthritis compared to healthy donors.…”
Section: Hpvmentioning
confidence: 99%
“…This channelling of glucose away from oxidative phosporylation towards glycolysis has been shown to reduce oxygen consumption in many hyperglycemic tissues (Graham et al 1981;Sutherland et al 1990;Rimmer & Linsenmeier 1993;Strodter et al 1995;Brazy & Chobanian 1996;Yang et al 1997) and is thought to be a result of mitochondrial damage secondary to the formation of reactive oxygen species (Luft 1994;Abu el-Asrar et al 1995-96;Kowluru et al 1997;Kristal et al 1997).…”
Section: Discussion I) Oxygen Uptakementioning
confidence: 99%